Ultrasound-controllable carbon monoxide nano-delivery systems for combined sonodynamic/gaseous therapies - Feng, Chong; Song, Shuang; Zhang, Xiaoyu; Wang, Jing; Meng, Qingxin; Wang, Tao (Frontiers in Bioengineering and Biotechnology, 2025)
IndroductionThe integration of sonodynamic therapy (SDT) and carbon monoxide (CO) presents a promising synergistic strategy in cancer therapy owing to the unique advantage of CO in SDT sensitization. However, the development of SDT-compatible CO-delivery nanosystems remain a substantial challenge.MethodsHere, we developed an ultrastable and controllable CO nanoreservoir system through the integration of chlorine e6 (Ce6)-loaded, cancer cell membrane coating and iron carbonyl (Fe3CO12)-bridged mesoporous silica bodies (Fe3CO12-MSNs), which was specifically engineered to simultaneously achieve SDT and ultrasound (US)-responsive sustained CO release. Owing to the stabilization of Fe3CO12 within the silica framework, Fe3CO12-MSNs not only decreased unwanted CO leakage during transport but also enabled US-responsive matrix degradation accompanied by sustained CO release at tumor sites, which prolongs the therapeutic window of CO and maximizes the synergy of SDT and CO therapy.Results and DiscussionThis nanoplatform-mediated combination therapies showed highly efficient antitumor effects and triggered a robust tumor-specific immune responses. When in combination with immune checkpoint blockers, the nanoplatform notably eradicate the breast cancer with low systematic toxicity. Overall, our work provides a promising nanoplatform with US-responsive and sustainable CO release for highly efficient and safe SDT/CO combined therapeis.